1983
DOI: 10.1017/s003329170005008x
|View full text |Cite
|
Sign up to set email alerts
|

Tardive dyskinesia: a 3-year follow-up study

Abstract: SynopsisA prospective study of tardive dyskinesia was carried out to gain information regarding the natural history of the condition and to identify risk factors. Out of an original cohort of 182 psychiatric patients receiving maintenance antipsychotic drugs 99 were available for reassessment after 3 years. In this follow-up group the point prevalence of oro-facial dyskinesia increased from 39% to 47% over the 3-year period. Twenty-two patients developed the disorder, while remission occurred in 14 others. Ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(19 citation statements)
references
References 24 publications
3
16
0
Order By: Relevance
“…When corrected for remissions, the mean annual incidence rate decreased to 2.9%. This incidence rate, which includes both patients who developed and remitted from TD over time, is similar to results found by other studies during the same time period [28, 29]. The cumulative incidence of treatment-emergent TD in the study by Kane et al [29] was 12% after 4 years and 40% after 8 years of neuroleptic exposure, which is similar to our finding of an annual incidence rate (corrected for remissions) of 3% for classical antipsychotics.…”
Section: Td In the Time Period Of Classical Antipsychoticssupporting
confidence: 90%
“…When corrected for remissions, the mean annual incidence rate decreased to 2.9%. This incidence rate, which includes both patients who developed and remitted from TD over time, is similar to results found by other studies during the same time period [28, 29]. The cumulative incidence of treatment-emergent TD in the study by Kane et al [29] was 12% after 4 years and 40% after 8 years of neuroleptic exposure, which is similar to our finding of an annual incidence rate (corrected for remissions) of 3% for classical antipsychotics.…”
Section: Td In the Time Period Of Classical Antipsychoticssupporting
confidence: 90%
“…Evidence favoring topographical subsyndromes has been derived in part from the results of multivariate statistical analysis (Kidger et al, 1980) and from observations of dierential responses to pharmacological interventions (Greil et al, 1985). In addition, and in agreement with the results of the present study, Barnes et al (1983) found that the severity of orofacial but not limb/truncal TD was positively associated with age. Similarly, an association has been noted between both the negative symptoms and the cognitive de®cits of schizophrenia and the orofacial, but not limb/truncal manifestations of TD (Waddington et al, 1987).…”
Section: Discussionsupporting
confidence: 86%
“…Validating the present study's design and choice of subjects, the use of this definition of treatment-emergent tardive dyskinesia revealed a 4.6% incidence of new cases among haloperidol-treated subjects, a rate remarkably consistent with predicted exposure-adjusted treatment-emergent tardive dyskinesia rates for conventional neuroleptic drugs reported in the literature (20). The annual rate of new cases per year, in similar at-risk patients, has been estimated at approximately 5% in several analyses (3,(21)(22)(23). It is not clear whether the incidence of treatment-emergent tardive dyskinesia is linear over a 12-month period, but, if it is, the annualized haloperidol incidence here approaches 8%.…”
Section: Discussionmentioning
confidence: 99%